Occupational hazard to on-road air pollution within passenger transport micro-environments: evidence from traffic congested areas in Colombo, Sri Lanka - Wittachchikoralalage Dona Chamila Niroshini Adikaram; Carukshi Arambepola (BMC Public Health)
Abstract Background Traffic-related on-road air pollution is a major contributor to outdoor air pollution globally, particularly in developing countries most often due to outdated vehicle technology, and weaker emission control regulations. Drivers providing passenger transport services are constantly at higher risk. This study investigated the exposure to air pollutants of transport microenvironments (TME) of such vehicles most popular in heavy-traffic congested areas in the district of Colombo, Sri Lanka. Methods A cross-sectional study was conducted in the TME of three vehicular types: three-wheeled taxi, non-AC bus and AC car. Randomly selected vehicles made 288 trips (96 by each vehicle type) of more than one hour on four pre-arranged weekdays on typical sunny days, on the same road with minimal off-road air pollution. Ambient and in-vehicular particulate matter (PM) concentrations were measured using real time monitors, while being driven under the same conditions. Results The average ambient PM2.5 concentration was 115.5 μg/m3 (SD = 6.2), representing fine particles in the ambient air. As a fraction of the total PM10 concentration (PM2.5/PM10), it was 0.83. In comparison, this fraction was 0.85 within three-wheeled taxis, 0.83 within non–AC buses and 0.93 within AC cars. PM10 and PM2.5 median concentrations were 456.3 μg/m3 (SD = 47.2) and 386.2 μg/m3 (SD = 26.7) within three-wheeled taxis, 292.1 μg/m3 (SD = 36.3) and 239 μg/m3 (SD = 20) within non–AC buses and 63.5 μg/m3 (SD = 7) and 59.2 μg/m3 (SD = 6) within AC cars, respectively. PM ratio (in-vehicular/ambient) was three-fold within three-wheeled taxis; two-fold within non–AC buses; and two times lower within AC cars (p < 0.001). When comparing the PM ratios between vehicles, it was seven times higher inside a three-wheeled taxi than in an AC car. Conclusions Compared to other TMEs, drivers of three-wheeled taxis were most vulnerable to on-road air pollution. Redesigning such vehicles for safer cabin environment is recommended.